Multifunction machines on combined rail-wheel motion for deletion the consequences of extraordinary situation on transport communications - Dovgyalo Владимир Александрович; Bochkaryov Дмитрий Игоревич; Polyanskij Л. Б. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
In the article has been adduction the analysis of constructions of combined rail-wheel motion mechanisms of multifunction machines, determined its future trends, suggested some technical decisions of movement increasing on different width of track railway roads and increasing of the reliability and enlargement the technological possibilities of this type machines.